2018
DOI: 10.1111/ctr.13204
|View full text |Cite
|
Sign up to set email alerts
|

Fortuitous benefits of living kidney donation: Diagnosis of serious medical conditions during the living donor evaluation

Abstract: The evaluation process can diagnose serious medical conditions in a significant minority of donors that would have otherwise been unrecognized. The benefit associated with the donor evaluation should be considered an important part of the consent process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…Some ineligible donor candidates appreciated the opportunity to identify medical conditions during workup. It is estimated that a new diagnosis of hypertension occurs during evaluation in 25% of ineligible donor candidates and incidental diagnosis of malignancy occurs in less than 1% of ineligible donor candidates . However, other ineligible donor candidates endured prolonged uncertainty and anxiety about their health because they felt they had little opportunity to discuss their results with clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ineligible donor candidates appreciated the opportunity to identify medical conditions during workup. It is estimated that a new diagnosis of hypertension occurs during evaluation in 25% of ineligible donor candidates and incidental diagnosis of malignancy occurs in less than 1% of ineligible donor candidates . However, other ineligible donor candidates endured prolonged uncertainty and anxiety about their health because they felt they had little opportunity to discuss their results with clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that a new diagnosis of hypertension occurs during evaluation in 25% of ineligible donor candidates 9 and incidental diagnosis of malignancy occurs in less than 1% of ineligible donor candidates. [29][30][31] However, other ineligible donor candidates endured prolonged uncertainty and anxiety about their health because they felt they had little opportunity to discuss their results with clinicians. We recommend ensuring transmission of all new health data to referring clinicians to ensure appropriate follow up, with the establishment of clear pathways for ineligible donor candidates to access follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…Además, de la misma manera que se ha reportado en los datos presentados, también hay evidencia previa de que el proceso de evaluación puede diagnosticar afecciones médicas en algunos cDR contando que, de otro modo, tal vez no se hubieran reconocido 44 y que algunas de ellas pueden ser no ser malignas y comunes entre la población 45 . Esto, a pesar de las connotaciones que pueda tener, se llega a entender como un beneficio indirecto para la persona candidata a donante de riñón al ampliar el conocimiento sobre el propio estado de salud y, si es preciso, iniciar las medidas oportunas de manera más temprana 44 .…”
Section: Discussionunclassified
“…This is slightly higher than previously published rates of 42%-54%. 7,10 The evaluation process revealed a medical condition requiring timely medical attention in 33.1% of the refused donor candidates and in 18.6% of all evaluated. The first study to describe unknown medical conditions in donors in 1993 has demonstrated an incidence of 8.4%, which is markedly lower.…”
Section: Discussionmentioning
confidence: 99%